CONSTITUTIONAL LAW-MAKING IN WARTIME: INSIGHTS AND FUNCTIONAL ANALYSIS - Lvova, Ielyzaveta (CEP USM, 2023)
The paper discusses general issues related to the respect of constitutional principles as essential sources of constitutional-law making in wartime in Ukraine. The research contributes to the development of the study of the issue of legislation by applying the existing concept of constitutional law-making. Enshrined in the Preamble of the Constitution of Ukraine, the state strategic course for Ukraine’s full membership in the European Union and the NATO provides for the strengthening of the rule of law through the implementation of this course by public authorities, courts and judges, the legitimization of their activities in accordance with the features of European constitutionalism, and the development of civil society under martial law. The study analyses the ensuring of the implementation of constitutional and legal norms both through state coercion and through legal awareness of the people of Ukraine. The relationship between the implemented legislation and the existing legal system under wartime in Ukraine. This study contributes to extant research by adopting the existing concepts of law and law-enforcement.
LVOVA, Ielyzaveta. Constitutional law-making in wartime: insights and functional analysis. In: Teoria și practica administrării publice: materiale ale conferinței ştiințifico-practice internaționale, ediţia a 27-a, 19 mai 2023, Chişinău. Chişinău: Centrul Editorial-Poligrafic al USM, 2023, pp. 157-161.
Keywords: democracy; constitutional law-making; Constitutional court; human rights; military aggression; rule of law; security; Ukraine; wartime